Drip fertigation influences yield, nutrient uptake and soil properties of peanut (Arachis hypogaea) - JAIN, N K; YADAV, R S; JAT, RAM A (The Indian Journal of Agricultural Sciences, 2021)
The present field experiment was conducted at ICAR-Directorate of Groundnut Research, Junagadh (Gujarat) for two consecutive summer of 2014 and 2015 to investigate the influence of drip fertigation on yield, nutrient uptake and soil properties of peanut (Arachis hypogaea L.) in Saurashtra region of Gujarat. There were 10 treatments including 100% normal fertilizers (NF) with surface method of irrigation as contral which were replicated three times. The study revealed that drip fertigation with 100% NF (T10) produced significantly higher pod yield over control and was at par with other treatments. However, haulm yield was significantly higher under the application of 100% WSF fertigation half at sowing and one-fourth each at 20 and 40 DAS (T4) over T6 to T9 and was at par with other treatments including control. Soil moisture status showed declining trend with successive increase in plant age but could not reach the level of significance. Drip fertigation with 100% NF (T10) registered markedly higher uptakes of N (114.4 kg/ha), P (30.5 kg/ha) and K (67.2 kg/ha) over all the treatments. As compared to initial status, available soil NPK status improved after harvest at all soil depths and showed declining trend with increase in soil depth. The study indicated the saving of 25% NPK fertilizers by adopting 75% WSF fertigation through drip irrigation at sowing in summer peanut with comparable yield.